Contribution of local area deprivation to cultural-linguistic inequalities in foetal growth restriction: Trends over time in a Canadian metropolitan centre - Auger, Nathalie; Park, Alison L.; Daniel, Mark (Health & Place, 2013)
This study investigated temporal trends in heterogeneity of foetal growth restriction across neighbourhood deprivation levels for two culturally distinct communities (Anglophones and Francophones) in a North American metropolitan centre. Inequalities in foetal growth restriction related to deprivation fell from 1989 to 2008 for Francophones, but initial improvements for Anglophones later reversed with a rise in poor foetal growth in the most materially disadvantaged and, unexpectedly, advantaged areas as well. Inequalities in foetal growth restriction related to neighbourhood material deprivation may be emerging in this minority Anglophone population. Potential mechanisms underlying these trends are discussed, as well as implications for perinatal health policy.

Stillbirth in an Anglophone minority of Canada - Auger, Nathalie; Daniel, Mark; Mortensen, Laust; Toa-Lou, Clarisse; Costopoulos, André (International Journal of Public Health, 2015)
Objectives We assessed trends in stillbirth over time for Francophones and Anglophones of Quebec, a large Canadian province with publically funded health care and an English-speaking minority. Methods We calculated stillbirth rates for Francophones and Anglophones, and estimated hazard ratios (HR) by decade from 1981 to 2010, adjusting for maternal characteristics. We analyzed temporal trends by gestational interval and cause of fetal death. Results Stillbirth rates decreased in Quebec during the three decades, due to improved rates in Francophones. Rates decreased for Anglophones in 1991–2000, but increased in 2001–2010 at term, during the second trimester, and for most causes of fetal death. In the 2000s, the hazard of stillbirth for Anglophones was nearly the same as the hazard for Francophones in the 1980s (HR 0.93, 95 % confidence interval 0.82, 1.05). Conclusions Stillbirth rates declined in both Francophones and Anglophones before the turn of the century, but increased thereafter for Anglophones, suggesting that linguistic inequalities in stillbirth may be emerging in Quebec. Linguistic status may be a useful marker for surveillance of inequalities in stillbirth.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.